Iran's nuclear program : emerging from political fallout. - Pang, Tee Meng. (2010)
The nuclear crisis in Iran has become a tough challenge for the global community as it tries to persuade a defiant Tehran to suspend its controversial enrichment program through the use of coercive diplomacy. However, this parochial focus on "carrots and sticks" in accordance to the spirit of the strategy to achieve success has been thwarted by geopolitical developments, which made Iran's continuing pursuit of its fuel-cycle interest remain an alluring option. This essay intends to capture geopolitical milestones that have nurtured Tehran 's political confidence towards confrontation instead of compromising even though potent backlashes, potential gains and lack of economic benefits should have dissuaded its defiance. The paper begins by analyzing deficiencies in rationalizing Iran's defiance that can complicate the effort to change Tehran's behavior before examining critical considerations that initially caused Tehran's confidence to be gravely corroded. Using important developments and events stemming primarily from the Iraq War, energy security, rising nationalism among Iranians on the nuclear issue and a new hardline government in Iran, the thesis will show how Tehran's confidence to restart its enrichment activities was revived and subsequently reinforced. Sensing an incoherent United Nations Security Council (UNSC) in formulating sanctions against Iran and seeing its own success in securing new energy contracts, their implications ultimately convinced the regime to pursue its nuclear aspirations in staunch defiance.